The importance of theory and history in understanding and developing the common law of contract – some further preliminary reflections - PHANG, Hon. Andrew (Institutional Knowledge at Singapore Management University, 2024)
In a previous essay, an attempt was made to demonstrate the important role that both theory and history play in helping us to understand and develop the common law of contract. As pointed out in that essay, a comprehensive treatment of the subject would require lengthy discourse in a book or even several books. This essay follows-up on that previous essay, again by way of preliminary reflections only, to correct the dominant perception that the development of the common law in general and contract law in particular is premised mainly on doctrinal development based on logic and analogy with the occasional reference to public policy. However, as is not unexpected in the context of imperfect knowledge in an imperfect world, whilst theory and history do often contribute to such development as well, this is not always the case.